Sistem Pendukung Keputusan Untuk Rekomendasi Topik Skripsi Dengan Metode Fuzzy AHP - Abdullah, Asrul; Sucipto, Sucipto (Jurnal Transformatika, 2021)
The ability to produce a scientific work both journals, scientific articles and thesis is needed to support the competence of undergraduate students in a university. The existence of a thesis course in a number of universities is one of the efforts to train students in producing a scientific work. To arrive at the stage of making a thesis, a student must first study various kinds of courses in each study program. Choosing a thesis topic is one of the most difficult stages in the preparation of a thesis. This is because there are still many students who do not understand and know their interest and ability in one of the courses which will later be used as a topic in thesis preparation. The focus of this research is a decision support system that is able to answer student problems in determining thesis topics according to their abilities. The method used is a waterfall within the SDLC (system development life cycle) framework starting from system requirement, data collection, design, implementation, testing, and maintenance. The result of this research is the ability of the decision support system to provide recommendations for thesis topics according to the abilities of students. The greatest weight is for A5 students for Computer Networking interest of 1,410 while the smallest weight is for A4 students for Multimedia interest of 0.080.